Realization of Intercultural Penetration Principle in the Professional Training of Specialists in Japanese Studies - A. V. Derkach (Vestnik MGIMO-Universiteta)
The article presents a research in exposing students of Japanese to the indigenous cultural environment. The analysis of modern theories in cultural interpenetration and intercultural adaptation let the author come to the conclusion that professional training of specialists in crosscultural intercourse at professional level makes it necessary to work out new teaching technologies. According to the author, they are to be aimed at preparing a specialist that can act as an intermediary in the intercultural community, thus possessing such qualities as empathy and ability of intercultural consensus.